Putty Capital and Clay Labor: Differing European Union Capital and Labor Freedom Speeds in Times of European Migration (Global Journal of Management and Business Research, 2016)
Globalization has led to unprecedented risks stemming from global interconnectedness. Economic trade may distribute benefits of international exchange unevenly due to fundamental barriers of distance, national borders and implicit market segmentation. In order to equalize more equitable trade prosperity, the European Union (EU) 4 freedoms of goods, services, capital and labor were established by a neoliberal policy framework and the Eurozone featuring a common currency. While there is a vital central monetary union and since the 2008/09 World Financial Crisis a common European fiscal pact, EU free movement is limited regarding labor mobility. This paper is based on the idea that the asymmetry of the mobility of labor and capital leads to the risk of an uneven distribution of gains within the European Union towards some core states against the periphery. In the light of the current European migration, the following paper offers a forward-thinking perspective on potential emergent risks arising within the European Union due to an asymmetry between the mobility of labor on the one hand and capital and goods on the other in times of mass migration.
Keywords: goods; services; capital and labor